Association of the IL-15 and IL-15Rα genes with celiac disease. (November 2017) - Escudero-Hernández, Celia; Plaza-Izurieta, Leticia; Garrote, José A.; Bilbao, José Ramón; Arranz, Eduardo; ,
Highlights: Two SNP located upstream the IL15 gene might be associated with celiac disease. The RP11-208N20.1 and IL15 region might have a role on cytokine regulation in CD. The IL15RA gene could be related to the age at diagnosis of CD patients. Abstract: Celiac disease is a chronic autoimmune condition triggered by dietary gluten in genetically predisposed individuals and the treatment is a strict gluten-free diet. The major predisposing genes are HLA-DQA1 and HLA-DQB1, but these are not sufficient for disease development. One of the candidate genes worth studying is interleukin (IL)-15 gene, together with its specific receptor, IL-15Rα, as they participate in promoting lymphocyte signaling and survival, and the establishment of appropriate conditions for villous atrophy, then acting as key players in the immunopathogenesis of CD. Here we analyze IL-15 and IL-15Rα genes in samples from the Spanish Consortium for Genetics of Celiac Disease (CEGEC) collection, identifying two regulatory single-nucleotide polymorphisms (SNP) that might be associated with celiac disease: rs4956400 (p-value 0.0112, OR 1.21, 95% CI 1.04–1.40) and rs11100722 (p-value 0.0087, OR 1.24, 95% CI 1.06–1.45), both located upstream the IL15 gene. When the expression of both genes was assessed, these two SNPs were found to be correlated with IL-15 higher protein expression. Besides, rs8177655 from IL15RA was also associated to mRNA IL-15 expression in CD patients. Finally, three SNPs from IL15RA intronic regions, rs2296141, rs3136614 and rs3181148, and another from its 3'UTR region, rs2229135, could be related to the age of diagnosis of celiac disease patients.